Evaluasi Pelaksanaan Rekapitulasi Hasil Penghitungan Suara Pemilihan Presiden Tahun 2019 di Komisi Pemilihan Umum Kota Palembang - Joni, Muhammad; Syaparman, Syaparman; Mardianto, Mardianto (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
The scope of the research is used as a limitation of the problem under study so that the research carried out does not deviate from the goal. To clarify the scope of the discussion, this research will focus on problems in accordance with the scope of the research. The scope of this research only focuses on the implementation of the 2019 Presidential Election Vote Count Recapitulation at the Palembang City General Election Commission. Based on the results of the research and discussion in the previous chapter, the following conclusions can be drawn: (1) The 2019 Presidential Election Vote Count Result Recapitulation has been going well but the existing human resources and infrastructure must be a record for policy making so that implementation a recap like this can run even better, furthermore regarding standard procedures there is a PKPU which regulates the process of recapitulating the results of the 2019 presidential election, but the Palembang City General Elections Commission can make innovations or work systems that do not violate existing rules but are able to create a burden. the work of the organizers under is more efficient and effective. (2). The problem in the 2019 Presidential Election Vote Count Recapitulation is the limited supporting facilities in the Implementation of the 2019 Presidential Election Vote Count Result Recapitulation At the Palembang City General Election Commission, a solution can be found by the Palembang City KPU, for the shortage of projectors the Palembang City KPU has borrowed a lease or the like.